New reports of species of Chaetomium and Humicola to Bahia state and Brazil - Rose Marie-Perle Gorguette; Cristiano Santana da Silva; Thaís Marcelo Souza; Jadergudson Pereira (Rodriguésia)
Abstract The present study brings the first report of species of Chaetomium and Humicola from Bahia state. Chaetomium globosum was isolated from different substrates of cacao, jackfruit, papaya and soursop and C. pseudoglobosum from cow dung. Humicola cuyabenoensis was isolated from soil samples of cacao plantations in the southeast Bahia.